Performance Characteristics of Conventional Vertical Cavity Surface Emitting Lasers VCSELs at 1300 nm - Faten Adel Ismael Chaqmaqchee (Zanco Journal of Pure and Applied Sciences, 2019)
Vertical-cavity surface emitting lasers (VCSELs) are interesting devices because of their low-cost manufacturing and testing methods, circularly shaped output beam for high coupling efficiency and suited for use in fiber-optic networks and as optical interconnects. In this paper, experimental results of output light-current-voltage (LIV), optically pumped VCSELs operating at 1320 nm wavelength are presented. The commercial device is biased just below threshold current of 0.84 mA under pump power of 1 mW. An amplified gain at around 20 dB is obtained. In addition, the influence of temperature on the performance of the device is studied.